Perceptual Advantages of People Living in Semeru Volcanic Areas, Indonesia: An MRCV (Multiple Response Categorical Variable) Analysis - Ariyanti, Yanti; Nila, Sarah; Nurhayu, Winati; Dubois, Dimitri; Arum Widayati, Kanthi; Atmowidi, Tri; Mettling, Clément; Raymond, Michel; Willinger, Marc; Suryobroto, Bambang (HAYATI Journal of Biosciences, 2026)
Why populations persist in active volcanic zones poses a fundamental challenge to risk perception models. We propose that perceptual advantages wherein tangible and intangible benefits filtered through local worldviews underpin this resilience. Through a thematic analysis of an open-ended question/answer study of communities in Mount Semeru, Indonesia, we identify six core frameworks of perceptual advantages. Analysis of Multiple Response Categorical Variable (MRCV) reveals that residents of high-risk zones cognitively amplify bio-cultural and livelihood benefits, showing significantly higher odds of emphasizing BIRTH/FAMILY (lineage/kin ties, birthright, and deep social networks that create an intergenerational connection to the land) and ECONOMIC (livelihood opportunities, including agriculture and volcano-driven tourism) advantages, while safe-zone residents prioritize ambient CLIMATE-related benefits (a preferred quality of life attributed to the region’s cool, fresh air and superior air quality). Crucially, the influence of gender is context-dependent, as significant disparities in perception vanish within the high-risk zone. In this environment, the shared experience of chronic volcanic threat supersedes gender distinction to foster a "community of fate". Within this collective, a shared risk-benefit calculus and a unified identity override individual perspectives. These findings demonstrate that persistence in hazardous environments reflects an active cognitive recalibration of risk and benefit, necessitating disaster policies that integrate these perceptual realities.